Saving does not finance Investment: Accounting as an indispensableguide to economic theory - Fabian Lindner (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
The paper analyses the accounting relationships between the financial and the real economy. It will be shown that accounting can clarify the nature of economic phenomena and be an important building block for economic theory. The paper will argue that there is much confusion about key macroeconomic concepts like saving, investment and finance. This confusion is best summarised in the statement "saving finances investment". After clearly defining the accounting relationships between lending, financial saving and physical investment it will be shown that this is a nonsense statement. The theory behind it - the loanable funds theory - will be analysed and critiqued. It will be shown that the loanable funds theory confuses the concepts of income and production, lending and saving, and financial saving and non-financial saving. It will further be shown that this has not only theoretical but also important policy implications.
urn:nbn:de:101:1-201211143729
Keywords: E21; E22; E23; E44; E50; 330; Saving; Wealth; Capital; Investment; Production; Financial Markets; Macroeconomics; Money and Credit